Endocrine care of transgender and gender-diverse adults: Swiss recommendations (Swiss Medical Weekly, 2026)
Transgender and gender-diverse individuals require standardised, evidence-based and culturally sensitive endocrine care. International guidelines such as those from the World Professional Association for Transgender Health (WPATH) and the Endocrine Society provide a strong foundation. These Swiss recommendations build on them and offer context-specific recommendations adapted to Switzerland’s healthcare system, insurance policies and social considerations.These recommendations were developed by the “Working Group Transgender” of the Swiss Society of Endocrinology and Diabetology (SSED/SGED) in collaboration with multidisciplinary experts. They primarily focus on gender-affirming hormone therapy, including indications, monitoring and long-term management. They also address fertility preservation, bone and sexual health, and relevant psychological and legal aspects.Interdisciplinary collaboration among endocrinologists, primary care providers, mental health professionals, reproductive specialists and surgeons is recommended to ensure cohesive patient-centred care.